Tramadol em caprinos: efeitos clínicos, farmacocinética e biodisponibilidade - Nunes, Talyta Lins (Universidade Federal Rural do Semi-Árido, 2017)
Tramadol is an atypical opioid analgesic widely used in humans and in the routine of the small animal clinic. Due to the lack of studies that determine its pharmacokinetic and pharmacodynamic characteristics, its use in production animals is restricted. The objective of this research was to evaluate the clinical, familial and bioavailability effects of tramadol in goats. The study was divided into two phases: the first one evaluated the clinical effects of tramadol at doses of 2 and 4 mg / kg intravenously; In the second stage, the bioavailability and pharmacokinetic parameters of tramadol and O-desmethyltramadol were evaluated after intravenous and intramuscular administration at a dose of 4 mg / kg. Opioid has been shown to be safe and effective in the control of orchiectomy pain and should be given every 6 and 8 hours at doses of 2 and 4 mg / kg. The intramuscular opioid has bioavailability of 62%. The data from this research provide information on tramadol and its metabolites, and serve as the basis for future studies involving the drug and the plasm
Tramadol in goats: clinical effect, pharmacokinetic and bioavaliability
Keywords: Analgesia; Pequenos ruminantes; Opioide; Analgesia; Small Ruminant; Opioid